New record in the diet of Philander andersoni - Niño-Reyes, Alejandra; González, Baltazar; Navarro-Morales, Alejandro; Moreno, Albeiro; Velásquez-Valencia, Alexander; Capera, Gover; Cepeda-Duque, Juan Camilo (Therya Notes, 2020)
Marsupial species of the family Didelphidae comprise the most diverse extant group of Metatherians inhabiting South America and part of North America. This family comprises more than 95 species, among which the members of the subfamilies Didelphinae and Caluromyinae include the largest species (> 150 g). Although widely distributed, information about their feeding habits is relatively scarce, especially for species of the genus Philander. Here we present the first record and description of a predatory event on the Tropical Flat Snake (Siphlophis compressus) by the Anderson’s Four-eyed Opossum (Philander andersoni) in the Amazonian region of Colombia. During the predation event, we made ad libitum observations for about 12 minutes, using a camera to record the feeding behavior of P. andersoni. The event was recorded on October 31, 2018. During a nocturnal survey, we observed one individual adult of P. andersoni while consuming a specimen of S. compres- sus. The marsupial bit and pulled the snake body with its premolar dentition and forelimbs respectively to consume the prey’s soft parts. This record shows that although S. compressus exhibits several antipredator characteristics, such as an aposematic elapid-like colored pattern, elu- sive behavior and Durvenoy glands, P. andersoni was able to feed upon this species in a stereotyped way. To the best of our knowledge this is the first documented consumption event of this snake by a mammal species, yielding new information about the feeding habits of P. andersoni and the predators of S. compressus. Appendix